Multistep creation of a criteria catalogue for sociotechnical transitions in agriculture - Madita Olvermann; Simone Kauffeld (Transformationsprozesse in Stadt und Land: Erkenntnisse, Strategien und Zukunftsperspektiven, 2024)
To address today's grand challenges, socio-technical transitions need to be designed in different sectors (e.g., agriculture). Technology assessment (TA) is a valuable tool to identify interactions and consequences of transition processes, but it requires an appropriate assessment system to develop guidelines. This article addresses the question of how to assess technological transitions in agriculture from a stakeholder perspective and presents a multi-step TA procedure inspired by a multi-criteria decision analysis exemplified by one transition: electrical farming. The procedure contains three steps. First, assessment criteria for the transition are identified in the context of a classical TA using stakeholder interviews. On this basis, a multidimensional catalogue of 24 criteria was created. Finally, criteria are validated and weighted according to their relevance with a second sample. The results provide recommendations for communicating and evaluating transitions in rural areas and the agricultural sector. – – Um den großen Herausforderungen unserer Zeit zu begegnen, müssen soziotechnische Übergänge in verschiedenen Sektoren (z. B. in der Landwirtschaft) gestaltet werden. Das Technology Assessment (TA) ist ein wertvolles Instrument, um die Wechselwirkungen und Folgen von Transitionsprozessen zu ermitteln, aber es erfordert ein geeignetes Bewertungssystem, um Leitlinien zu entwickeln. Dieser Artikel untersucht die Frage, wie technologischer Wandel in der Landwirtschaft aus der Perspektive von Steakholdern bewertet werden kann und stellt ein mehrstufiges TA-Verfahren vor, das sich an einer multikriteriellen Entscheidungsanalyse orientiert, die am Beispiel der elektrifizierten Landwirtschaft erläutert wird. Das Verfahren besteht aus drei Schritten. Zunächst werden im Rahmen einer klassischen TA mittels Stakeholder-Interviews Bewertungskriterien für die Transition identifiziert. Auf dieser Grundlage wird ein multidimensionaler Katalog von 24 Kriterien erstellt. Schließlich werden die Kriterien mit einer zweiten Stichprobe validiert und nach Relevanz gewichtet. Die Ergebnisse ergeben Empfehlungen für die Kommunikation und Bewertung von Wandelprozessen in ländlichen Räumen und im Agrarsektor.
urn:nbn:de:0156-1171152; hdl:10419/285312; https://econpapers.repec.org/RePEc:zbw:arlfob:285312
Keywords: 710; Agriculture; Technology Assessment; Participation; Energy Transition; MCDA; Transition Process; Landwirtschaft; Technology Assessment; Partizipation; Energiewende; Wandelprozesse